The naming of Guthlac - Cavill, Paul (Brepols, 2015)
This study discusses the passages in Felix’s Vita Sancti Guthlaci which refer to the naming of the saint. It suggests that Felix’s ideas as to the source and meaning of the name are problematic in that they do not obviously reflect vernacular naming patterns and they were not passed on by Old English writers. It is argued that this might be because Felix’s obscure Latin has been mistaken, and that he might have wanted to refer to Guthlac’s ‘land’ and ‘tribe’ not as the source of his name, but as being named after him. It is pointed out that Felix’s vocabulary in the naming passages bears striking resemblance to that in a passage of Jerome’s translation of the Regula Pachomii which relates it to desert monasticism, the dominant paradigm for Felix’s hagiography.